The creation of performance funding in Michigan: Partnership, promotion and points - Renata Opoczynski (Arizona State University, 2016)
While accountability in higher education has been a topic of debate for decades, in recent years the discussions have shifted to emphasize efficiency and economic measures of success. A prominent example of this accountability movement is the increase in popularity of performance funding policies. One of the most recent states to implement performance funding is Michigan, which began their performance funding policy in 2012. This study explored the creation and implementation of the state of Michigan's performance funding policy. In particular, the decision making processes institutional administrators and state leaders engaged in while designing, promoting, and implementing the policy. Using a case study design and interviewing both higher education administrators and state leaders who were involved in the creation of the performance funding policy in Michigan yielded five large trends: 1) The importance of advocacy coalitions; 2) Securing support through a focus on higher education affordability; 3) Concerns with how to measure data and compare institutions; 4) Insufficient financial incentives; and 5) Limited impact on institutional decision making.